Eleven percent : a novel - Uthaug, Maren, 1972- (St. Martin's Press, 2025)
"An inverse The Handmaid's Tale that asks: What if women took over the world? It is the New Time, a time not so different from our own except that the men are gone. All but eleven percent of them, that is, the minimum required to avoid inbreeding. But they are safely under lock and key in "spa" centers for women's pleasure (trained by Amazons to fulfill all desires) and procreation. A few women protest that the males should be treated better -- more space, better food, but all agree that testosterone cannot be allowed to roam free. The old patriarchal cities are crumbling, becoming overgrown; people now live in "round communities." But if you prefer the slum, that's okay too. Religion has survived, sort of: women priestesses speak in tongues, inspired by snake venom, as apples are passed around to the congregation. But all social engineering has its costs ... Four different lives intersect: Medea, a tiny, long-haired witch and snake whisperer; Wicca, a young priestess who excelled at the "self-pleasuring" curriculum in school and has lost her pregnant lover; Eva, a doctor working in a spa center, and Silence, who lives in an almost abandoned convent. Each will discover the cracks in this women's paradise. Provocative, irreverent, and completely riveting, Eleven Percent -- a #1 bestseller in Denmark -- is the first novel to appear in English by celebrated Danish author Maren Uthaug." --